Contemporary Agrarian Legal Policy in Indonesia - Muhammad Ridwan Murtiyanto; Moh Indra Bangsawan (Proceeding International Conference Restructuring and Transforming Law, 2023)
The implementation policy of Law Number 5 of 1960 concerning Basic Agrarian Regulations (UUPA) focuses on serving many people, especially farmers, who make up the majority of Indonesia's population experiencing economic difficulties. At that time, agrarian reform rules began to be implemented which included restrictions on ownership of agricultural land, prohibition of inactive landowners, redistribution of land affected by agrarian reform and mortgage owners of agricultural land. Apart from that, the eradication of colonial rights was also carried out and changes in legal provisions governing previous land ownership became new rights in accordance with the UUPA. Reforms in the field of land law continue to be needed and carried out by the community, but the government has so far maintained the legitimacy of the BAL by trying to adapt to the current reform conditions. The purpose of this research is to understand the political development of national agrarian law in Indonesia and how the direction of development and reform of national agrarian law is. This is related to efforts to create jobs. The research method used is descriptive‐qualitative using secondary data sources. Since the enactment of the BAL, the political development of national agrarian law has experienced ups and downs in its application. Agrarian reform is an unavoidable need to realize justice in an effort to improve people's welfare, especially farmers, fishermen and indigenous peoples, which must be accompanied by reform of agrarian law in Indonesia.